The Role of Neoadjuvant Therapy to Improve the Extent of Resection in “Unresectable” Gliomas - Jacobo, Javier A.; Mejia-Perez, Sonia; Moreno-Jimenez, Sergio (World neurosurgery, 2021)
Surgical resection plays a pivotal role in the management of glial tumors and a greater extent of resection (EOR) should be the goal in most surgeries to improve overall survival. Many factors may limit the EOR. A potential role for preoperative chemotherapy to decrease the volume and/or infiltration of gliomas, thereby facilitating a safe radical resection, has been recently suggested. This review aims to provide an overview of the current state of neoadjuvant therapy in the field of glioma surgery. A systematic review was conducted according to PRISMA guidelines to identify articles of low- and high-grade gliomas that received neoadjuvant chemotherapy prior to surgery to improve the EOR from 2000 to 2020. Full-text articles that addressed this subject were included for evaluation. Case reports and clinical trials have been published for the use of chemotherapy as a neoadjuvant therapy to improve surgical resection in low-grade gliomas. More scarce information exists regarding this strategy for high-grade glioma surgery. Neoadjuvant chemotherapy has played a role in overcoming obstacles that limit the EOR in patients with complex gliomas, especially low-grade gliomas.